2000
DOI: 10.1024//0253-4533.19.12.31
|View full text |Cite
|
Sign up to set email alerts
|

Word order effects in German sentences and German pseudo-word sentences

Abstract: Summary: German belongs to those languages that allow a free permutation of subject, direct object and indirect object in verb final sentences. Five linear precedence (LP) principles have been postulated to describe preference patterns for the different word orders ( Uszkoreit, 1986 ). The present study tested if these rules are valid for meaningful German sentences only or also hold for pseudo-word sentences, i.e., if they are independent of semantic language aspects. Twelve students saw sentences in six diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…The bilateral rather than left‐lateralized activation of the classical language areas in the blind supplements earlier electrophysiological findings (Röder et al ., 2000). It could be hypothesized that the use of Braille, similar to the use of sign language in the deaf (Neville et al ., 1998), results in a stronger engagement of the right hemisphere for language processing, because Braille also relies more upon spatial components than printed or spoken language (Hermelin & O'Connor, 1971; Karavatos et al ., 1984).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The bilateral rather than left‐lateralized activation of the classical language areas in the blind supplements earlier electrophysiological findings (Röder et al ., 2000). It could be hypothesized that the use of Braille, similar to the use of sign language in the deaf (Neville et al ., 1998), results in a stronger engagement of the right hemisphere for language processing, because Braille also relies more upon spatial components than printed or spoken language (Hermelin & O'Connor, 1971; Karavatos et al ., 1984).…”
Section: Discussionsupporting
confidence: 87%
“…Due to the case markers (der, dem and den) German allows a permutation of the order of the noun phrases: subject, indirect and direct object (S, IO and DO) without changing the literal meaning of a sentence. However, any deviation from the canonical word order (S–IO–DO) increases comprehension time and thus different noun phrase permutations can be used to systematically vary syntactic processing difficulty both for semantic and nonsemantic speech (for more details see Röder et al ., 2000; Röder et al ., 2002b). Here, we contrasted the syntactically most easy sequences (S‐IO‐DO, S‐DO‐IO) with the most difficult sequences (IO‐DO‐S, DO‐IO‐S).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ungrammatical fillers were of a similar form as the critical sentences but contained an incorrectly positioned participle. As previous studies have shown that sentences involving multiple permutations are judged to be very close to unacceptable on multipoint judgment scales [e.g., Fiebach et al, 2004; Pechmann et al, 1996; Röder et al, 2000], participants were thus confronted with 102 acceptable sentences (conditions N‐SO, P‐SO, and P‐OS), 68 sentences of a markedly degraded acceptability (condition COMB and the filler sentences), and 34 sentences of medium acceptability (condition N‐OS). Finally, 34 null events (empty trials) were introduced to improve statistical evaluation of the data [Miezin et al, 2000], thus resulting in a total number of 238 trials per participant.…”
Section: Methodsmentioning
confidence: 95%
“…These considerations, which are standard in the theoretical literature on German [Hoberg, 1981; Lenerz, 1977, 1993; Müller, 1995; Wöllstein‐Leisten et al, 1997], are also supported by a number of empirical findings using a variety of experimental methods. On the one hand, sentences such as Sentence 1 are judged to be less acceptable than are their subject‐initial counterparts [e.g., Pechmann et al, 1996; Röder et al, 2000], engender higher activation in the pars opercularis of the left IFG (i.e., part of Broca's region [Fiebach et al, 2004; Röder et al, 2002]), and elicit a left, frontocentral negativity in terms of event‐related brain potential (ERP) measures at the position of the permuted object [Bornkessel et al, 2002; Rösler et al, 1998; Schlesewsky et al, 2003]. In striking contrast to these findings, the permutation of object pronouns (as in Sentence 2) leads neither to a comparable reduction of sentence acceptability [Bader and Meng, 1999], nor to any ERP effect in comparison to subject‐initial control sentences [Schlesewsky et al, 2003].…”
Section: Introductionmentioning
confidence: 99%